Perkembangan Fikih dalam Era Digital: Kajian terhadap Metode Ijtihad dalam Memahami Masalah Kontemporer - Asep Supriatna (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
In the digital era marked by advancements in digital technology and globalization, the development of Islamic jurisprudence (fiqh) faces significant challenges. This research aims to uncover the crucial role of the ijtihad method in the context of understanding and formulating legal views on contemporary issues arising in the digital age. The research methodology employed is normative research, involving theoretical, philosophical, and jurisprudential analyses within Islamic fiqh. The study investigates the impacts of the digital era and shifts in the global paradigm on the development of Islamic jurisprudence. The primary focus of the research is to explore how the ijtihad method can adapt to the context of digital technology and the challenges of modern ethics. The research underscores the importance of adaptation and a profound understanding of Islamic law to address the changing times. The results of this research provide valuable insights into how Islamic jurisprudence can remain relevant in addressing contemporary issues that continue to evolve in the dynamic digital era. This study summarizes efforts to maintain the relevance of Islamic law and provide legal perspectives that align with the contemporary dynamics at hand.